Institutions and economic performance: What can be explained? - Simon Commander; Zlatko Nikoloski (Institute for the Study of Labor (IZA), 2010)
Institutions are now widely believed to be important in explaining performance. In this paper, we analyze whether commonly used measures of institutions have any significant, measurable impact on performance, whether of countries or firms. We look at three 'levels' of institutions and associated conjectures. The first concerns whether the political system affects performance. The second concerns whether the business and investment environment affects the performance of countries and the third concerns whether perceived business constraints directly affect the performance of firms. In all instances, we find little evidence of a robust link between widely used measures of institutions and our indicators of performance. We consider why this might be the case and argue that mis-measurement, misspecification, complexity and non-linearity are all relevant factors.
Keywords: D24; L21; O12; P48; 330; institutions; growth; Institutionalismus; Institutionelle Infrastruktur; Wirtschaftswachstum; Unternehmensentwicklung; Wirkungsanalyse; Welt